Oral health outcomes for people with cerebral palsy: a scoping review protocol. (December 2019) - Lansdown, Karen; Smithers-Sheedy, Hayley; Mathieu Coulton, Kimberly; Irving, Michelle
ABSTRACT: Objective: This review aims to systematically map the literature reporting on oral health outcomes experienced by people with cerebral palsy. Introduction: At present, there are no documented systematic reviews reporting on oral health outcomes for people of all ages with cerebral palsy. Subsequently, there are no clear guidelines, frameworks or detailed oral health recommendations for people with cerebral palsy. Considering the importance of oral health on general well-being and quality of life, it is important that it is not overlooked when focusing on patient-centered care for people with cerebral palsy. Inclusion criteria: Studies that focus on oral health, including dental diagnosis, trauma and/or treatment, facial pain, saliva, and sleep apnea, and/or make statements regarding oral health pertaining to cerebral palsy will be considered for inclusion inthis scoping review. Methods: This review will be conducted in accordance with the guidelines outlined by JBI methodology for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). Articles published in any language will be considered for inclusion, with no restriction on publication date. The search databases will include the Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, Scopus, Embase and Dentistry and Oral Science. A search of gray literature will also be conducted. Extracted data relevant to the scoping review will be performed by two reviewers.